Pengembangan Bahan Ajar Elektronik Energi dan Momentum Terintegrasi STEM Untuk Meningkatkan Hasil Belajar Siswa SMA - Yuni Fitria; Asrizal Asrizal (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
Industrial revolution 4.0 makes a major contribution to life. The era of the industrial revolution 4.0 requires human resources that can compete in the global economy. STEM education plays an important role in increasing students' creativity to compete in the future. The facts found in the field, activities that support student creativity in learning have not been carried out properly. The teaching materials used have not improved student learning outcomes optimally. The solution to overcome these problems was to develop STEM-integrated electronic teaching materials. This research method was Research and Development (R&D). This study aims to determine the effectiveness of STEM integrated electronic teaching materials. Test the effectiveness of teaching materials using experiments before-after conducted in one experimental class. The significance of the effectiveness of using electronic teaching materials on learning outcomes was analyzed by normality test, homogeneity test, and t-test. Based on the data analysis, it was concluded that STEM integrated electronic teaching materials were effectively used in physics learning to improve the learning outcomes of X grade students.